Limited-angle tomography applied to biological objects - Krauze, Wojciech; Kujawińska, Małgorzata (Photonics Letters of Poland, 2013)
Optical limited-angle tomography is strongly required in biological applications, as often there is an access to projections gathered from a small angle range. Choosing a reconstruction algorithm among many available is always a tradeoff between speed of calculation and quality of reconstruction. In this paper we present the studies how the a priori information about object’s geometry influences efficiency of the Data Replenishment Algorithm. The analysis is based on tomographic reconstruction of real biological cell of human malignant lymphoma. Full Text: PDF References S. Kou, C. Sheppard, "Image formation in holographic tomography", Opt. Lett. 33, 2362 (2008). CrossRef J. Hsieh, Computed Tomography Principles, Design, Artifacts, and Recent Advances (Wiley 2009). S. Isikman et al., "Lens-free optical tomographic microscope with a large imaging volume on a chip", P. Natl. Acad. Sci. USA 108, 7296 (2011). CrossRef S. Vertu, E. Maeda, J. Flügge, J. Delaunay, O. Haeberlé, "Comparison of resolution in tomographic diffractive microscopy using combinations of sample rotation and illumination rotation", Proc. SPIE 7904 (2011). CrossRef A. Likhachov, "Projection data replenishment algorithm for limited angle tomography", Optoelectron. Instrum. Data Process. 45, 55 (2009). DirectLink R. Gordon, "A tutorial on art (algebraic reconstruction techniques)", IEEE T. Nucl. Sci. 21, 78 (1974). CrossRef A. Andersen, A. Kak, "Simultaneous Algebraic Reconstruction Technique (SART): A Superior Implementation of the Art Algorithm", Ultrasonic Imaging 6, 81 (1984). CrossRef D. Verhoeven, "Limited-data computed tomography algorithms for the physical sciences", Appl. Optics 32, 3736 (1993). CrossRef J. Fessler, B. Sutton, "Nonuniform fast Fourier transforms using min-max interpolation", IEEE T. Signal Proces. 51, 560 (2003). CrossRef Z. Wang, A. Bovik, "A universal image quality index", IEEE Signal Proc. Let. 9, 81 (2002). CrossRef M. Kujawińska et al., "Problems and Solutions in Tomographic Analysis of Phase Biological Objects", Fringe 2013, 671 (2013) CrossRef